Numerical Analysis of Deterministic Micro-Textures on the Performance of Hydrodynamic Journal Bearing. (2018) - Shinde, Anil; Pawar, Prashant; Gaikwad, Sunil; Kapurkar, Ranjit; Parkhe, Avinash
Abstract: Now-a-days a lot of thrust is given on the research related to geometrical modifications of hydrodynamic lubricated bearing systems. Introducing deterministic micro-textures on the journal surface is considered to be one of the key approaches for improving the bearing performance. In this paper, bearing performance analysis is done without considering the effect of cavitation to study the effect of different triangular, circular and rectangular micro-textured grooves and ribs on the hydrodynamic journal surfaces using COMSOL Multiphysics software. Initially, the static performance analysis is carried out for hydrodynamic journal bearing system with smooth surface using thin fluid film analysis method and the results of the same are validated using analytical results. In the later part of the paper, the numerical analysis is carried out for different micro-textured journal surfaces. The simulation results of these studies shows that the value of maximum fluid pressure and frictional power loss are significantly affected by introduction of these deterministic micro-textures. Bearing with rectangular micro-textured ribs on the journal surface resulted in maximum pressure is development and frictional power losses as compared with other deterministic micro-textures. Similarly the rectangular micro-texture grooves gave minimum pressure development and frictional power losses as compared with other deterministic micro-textures.